Effect of light and pH on Pandarina morum and chlorella vulgaris cell culture growth and heavy metals sequestration rate - Othman, Rashidi; Shaharuddin, Ruhul Izzati; Wan Sulaiman, Wan Syibrah Hanisah; Hj. Baharuddin, Zainul Mukrim (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Bioaccumulation agent is an attracting alternative for wastewater treatment. However, the real situation for wastewater treatment is more complicated due to the presence of multiple metal ions. Algae represent the best green technology agent for wastewater treatment as they fix atmospheric N2, catalyze the nutrient cycling, suppress the growth of pathogenic microorganisms in soil and water, and also produce some bioactive compounds. In this study, two green algae species biogenesis is investigated in cell culture model system for rapid initiation and analysis by providing stringent control of genetic, developmental and environmental factor. The value of this experiment system is then analyzed by Inductively Coupled Plasma (ICP) by assessing the effect of pH on both green algae species growth as well as heavy metals sequestration rate. Six heavy metals (Pb, Fe, Cr, Cd, Al, and Cu) treatments and three different periods of time (week 1 until week 3) were observed. The results from this study suggest that C. vulgaris stated highest BCF value in Cr and Pb with 12 and 10 respectively. In another hand, P. morum has no response towards all treatments. A regulatory step for the green algae species growth biogenesis is controlled by pH whereas genotype and type of heavy metals appears to be a key factor for heavy metal sequestration rate efficiency.